Mindfulness, Trust, and Leader Effectiveness: A Conceptual Framework - Stedham, Yvonne; Skaar, Theresa B. (Frontiers in Psychology, 2019)
In this conceptual research, the authors develop an integrative framework for the relationship between mindfulness and leader effectiveness. Mindfulness is suggested to affect leader effectiveness via its impact on leader characteristics and behaviors that enable trust based relationships between the leader and followers. The paper provides detailed overviews of trust and mindfulness and their relationship to leadership. In-depth theoretical reflections on the linkages among the relevant concepts are offered. Of particular interest are the relationships between mindfulness mechanisms, leader characteristics and behaviors, and trustworthiness and trust.